1988
DOI: 10.1126/science.2455347
|View full text |Cite
|
Sign up to set email alerts
|

GABA A -Receptor Function in Hippocampal Cells Is Maintained by Phosphorylation Factors

Abstract: Gamma aminobutyric acid (GABA) mediates fast synaptic inhibition in the central nervous system by activating the chloride-permeable GABAA channel. The GABAA conductance progressively diminishes with time when the intracellular contents of hippocampal neurons are perfused with a minimal intracellular medium. This "run down" of the GABA-activated conductance can be prevented by the inclusion of magnesium adenosine triphosphate and calcium buffer in the intracellular medium. The amount of chloride conductance tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
129
4

Year Published

1990
1990
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(141 citation statements)
references
References 34 publications
8
129
4
Order By: Relevance
“…The results demonstrated that the rate of run-down was dependent on the concentration of GABA used to activate the cell reponse. In contrast, our studies show that run-down of the GABAA response in the hippocampus is independent of the concentration of agonist applied since the run-down still occurred without GABA application (Stelzer & Wong, 1987;Stelzer et al 1988). The differences in the result could be due to variations in experimental conditions or the GABAA receptor structure in the two types of neurones.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…The results demonstrated that the rate of run-down was dependent on the concentration of GABA used to activate the cell reponse. In contrast, our studies show that run-down of the GABAA response in the hippocampus is independent of the concentration of agonist applied since the run-down still occurred without GABA application (Stelzer & Wong, 1987;Stelzer et al 1988). The differences in the result could be due to variations in experimental conditions or the GABAA receptor structure in the two types of neurones.…”
Section: Discussioncontrasting
confidence: 40%
“…as the reversal potential of the (GABA-activated current remained constant throughout the time course of recording (Stelzer et al 1988).…”
Section: Resultsmentioning
confidence: 99%
“…To determine possible mIPSC rundown 18 , we followed cells over the same time course as in the Ca 2+ -free experiments without changing the external solution ('sham experiments'). No significant change occurred in the mIPSC amplitude ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Experiments investigating the pharmacology of the GABA response in spinal neurones were postponed for 10-20min, sufficient time for GABA-activated currents to become consistent in amplitude. The phenomenon of GABA-evoked current rundown was not quantified in this study but has previously been documented and is believed to be caused by the loss of ATP from the intracellular milieu due to dialysis by the recording electrode (Stelzer et al, 1988;Song & Huang, 1990). In contrast to currents activated by GABA, those evoked by glycine did not run down during the course of the experiments (n = 38).…”
Section: Propofol Modulation Of Gabaa Receptors Exhibits Membrane Asymentioning
confidence: 99%